Combining acetone-butanol-ethanol production and methyl orange decolorization in wastewater by fermentation with solid food waste as substrate. (December 2021) - Liu, Jingyun; Fan, Senqing; Bai, Ke; Xiao, Zeyi
Abstract: Simultaneously producing acetone-butanol-ethanol (ABE) and decolorizing Methyl orange (MO) by fermentation with solid food waste (SFW) was studied. During the batch fermentation with MO concentration from 100 mgL −1 to 1000 mgL −1, carbon source utilization efficiency was above 93% with yields of acetone, butanol and ethanol being 0.13 gg -1, 0.23 gg -1 and 0.04 gg -1, respectively. During the repeated fermentation with the bagasse as the cell immobilization material, carbon source utilization efficiencies were all above 90% in the first 5 cycles fermentation. The maximum butanol and ABE concentration were 12.8 gL -1 and 22.1 gL -1, respectively. The solvent yield of acetone, butanol and ethanol were around 0.13 gg -1, 0.25 gg -1 and 0.06 gg -1, respectively. The MO decolorization had no negative effect on the ABE production and the decolorization efficiencies were all above 99% during batch fermentation or repeated fermentation with electrons transferred from intracellular to extracellular by mediator with the help of azo reductase to decolorize MO. Graphical abstract: Image 1 Highlights: ABE fermentation and wastewater treatment containing MO were combined. Solid food waste was used to simultaneously produce ABE and decolorize MO. MO decolorization efficiencies are above 99% in the range of 100–1000 mgL-1. Maximum butanol and total ABE concentration were 12.8 gL-1 and 22.1 gL-1 respectively. Cells can be used for 7 cycles with stable decolorization-fermentation performance.